Mengukur Ketahanan Keuangan Dan Kinerja Keuangan Menggunakan Metode Economic Value Added (EVA) Dan Financial Value Added (FVA) Pada PT KAI (Persero) - Nathasyah Putri Maharanni; Yenni Samri Juliati Nasution; Isnaini Harahap (Jurnal Riset Akuntansi, 2025)
This study aims to analyze the financial resilience and financial performance of PT KAI (Persero) during the 2020–2024 period using Economic Value Added (EVA) and Financial Value Added (FVA) as measurement tools to assess the company's economic and financial value creation. This research employed a quantitative descriptive approach using secondary data obtained from the annual reports and financial statements of PT KAI (Persero) for the 2020–2024 period. The data were analyzed through EVA and FVA calculations to evaluate the company's ability to generate added value while considering the cost of capital and the effectiveness of asset utilization. The results indicate that PT KAI (Persero) experienced a substantial increase in total assets from IDR 53.21 trillion in 2020 to IDR 97.10 trillion in 2024, accompanied by revenue growth during the post-pandemic recovery period, reflecting improvements in financial conditions and operational capacity. These findings support previous studies suggesting that value-based performance measurement provides a more comprehensive assessment than conventional financial analysis because it incorporates the cost of capital and the ability of assets to create economic value. It can be concluded that EVA and FVA are relevant methods for assessing financial resilience and financial performance. Therefore, the company should continuously improve the efficiency of capital and asset utilization, while future studies are encouraged to integrate EVA and FVA with other financial resilience indicators to obtain a more comprehensive evaluation.